If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 16 = 6x + 198 Reorder the terms: 16 + 3x = 6x + 198 Reorder the terms: 16 + 3x = 198 + 6x Solving 16 + 3x = 198 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 3x + -6x = 198 + 6x + -6x Combine like terms: 3x + -6x = -3x 16 + -3x = 198 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + -3x = 198 + 0 16 + -3x = 198 Add '-16' to each side of the equation. 16 + -16 + -3x = 198 + -16 Combine like terms: 16 + -16 = 0 0 + -3x = 198 + -16 -3x = 198 + -16 Combine like terms: 198 + -16 = 182 -3x = 182 Divide each side by '-3'. x = -60.66666667 Simplifying x = -60.66666667
| 8x-4+6x+15=14x+11 | | 20/-d=13 | | 17+d=20 | | 14+4a=a+4-8 | | x+y(4)=120 | | 1+2n=-10+5-n+4n | | J-1.2(.4-.1j)=2.88 | | 0.4x=60 | | Bx+9=3y | | 5y+20=7x-56 | | x/5-7/4=x/10-1/20 | | -6n-5n=-16-7n | | 9/22=x/176 | | Ar=3r+14 | | 34=x/64 | | 63-f=52 | | K-8=5k-k-5 | | .2I+4(.3+.2I)=2.2 | | 14x+2=9x+20 | | 0.1x+0.2x=6 | | -(12-t)+(2t-4)= | | 17*v/v=7 | | 13/21=x/147 | | 6(x+9)=60 | | 1+2r-r=11+3r | | 12*c=156 | | 4y=-6+4x | | 1+1+5x-8=5x+x | | 90=(x-2)(y-1.5) | | 12/5=x/45 | | (4i)(-8+8i)= | | 5.3x=4.1x+5.76 |